PENERAPAN SAN REMO MANUAL PADA PENGIRIMAN (SATGAS MTF) TNI DALAM MISI UNIFIL - Retno, Martha Latu (Jurnal Mahasiswa Fakultas Hukum, 2015)
Abstract At the year of 2009 for the first time Indonesia took part by send a warships (KRI) for peacekeeping mission in UNIFIL (United Nations Mission Interim Forces in Lebanon). The UNIFIL MTFs mission acted upon military operations other than war at sea were located in the area of ââconflict between Israel and Hezbollah. International legal provisions applicable to war at sea is the San Remo Manual which is a guideline for the implementation of war at sea. Therefore, it is necessary to study the legal status and how the implementation of the San Remo Manual can be used in military operations in the Task Force MTF UNIFIL mission. The purpose of writing is to examine and analyze the legal status of the Task Force and the military MTF identify and analyze the implementation of the San Remo Manual can be used in military operations in the Task Force MTF UNIFIL mission. This writing method normative legal writing approach Statute and philosophical approach. Of this paper will be the writing on the analysis results obtained legal status and application of the military task force MTF San Remo Manual can be used in the operation of the Task Force of UNIFIL MTF. Key words: legal status of The MTF TNIâs task force, Â the implementation of the san remo manual Â Abstrak Â Pada tahun 2009 untuk pertama kalinya Indonesia mengirimkan Kapal Perang Republik Indonesia (KRI) dalam misi pemelihara perdamaian di bawah bendera PBB pada misi United Nation Interim Forces Mission in Lebanon (UNIFIL). Di dalam Satgas MTF TNI misi UNIFIL ini malaksanakan operasi militer selain perang di laut yang berada didaerah konflik antara Israel dan Hisbullah. Ketentuan hukum InternasionalÂ yang berlaku untuk perang di laut adalah San Remo Manual yang merupakan pedoman pelaksanaan perang di laut. Tujuan penulisan ini untuk mengetahui dan menganalisa status hukum Satgas MTF TNI serta mengetahui dan menganalisa penerapan San Remo Manual dapat digunakan dalam operasi Satgas MTF TNI dalam misi UNIFIL. Penulisan ini menggunakan metode penulisan hukum normatif yang menggunakan pendekatan undang-undang dan pendekatan filsafat. Dari penulisan ini akan diperoleh hasil penulisan mengenai analisis status hukum Satgas MTF TNI dan penerapan San Remo ManualÂ dapat digunakan dalam operasi Satgas MTF UNIFIL. Kata kunci: status hukum Satgas MTF TNI, penerapan san remo manual